2010
DOI: 10.1089/vim.2009.0102
|View full text |Cite
|
Sign up to set email alerts
|

Persistent Effect of IFNAR-1 Genetic Polymorphism on the Long-Term Pathogenesis of Chronic HBV Infection

Abstract: Genetic polymorphism of IFNAR-1 plays a large role in determining the clearance or chronicity after hepatitis B virus (HBV) exposure. However, it is not clear whether type I interferon receptor-1 (IFNAR-1) variations continuously exert their effects to influence the final outcomes following HBV chronicity, including acute-on-chronic hepatitis B liver failure (ACLF-HBV), chronic hepatitis B (CHB), liver cirrhosis (LC), and hepatocellular carcinoma (HCC). Here we report that these four potential outcomes of chro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
33
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(33 citation statements)
references
References 41 publications
0
33
0
Order By: Relevance
“…Both type I and II IFNs, as well as proinflammatory cytokines such as interleukin-6, are induced in response to HBV infection. Moreover, deficiencies in the innate immunity tampered with the control of HBV infection (10,12,37,38). Using hydrodynamics-based transfection in a series of knockout mice, Yang et al demonstrated the involvement of innate immunity-related effectors in the HBV clearance, including IFN-␣/␤ receptor 1, IFN-␥, and tumor necrosis factor (TNF) receptor 1 (35).…”
Section: Discussionmentioning
confidence: 99%
“…Both type I and II IFNs, as well as proinflammatory cytokines such as interleukin-6, are induced in response to HBV infection. Moreover, deficiencies in the innate immunity tampered with the control of HBV infection (10,12,37,38). Using hydrodynamics-based transfection in a series of knockout mice, Yang et al demonstrated the involvement of innate immunity-related effectors in the HBV clearance, including IFN-␣/␤ receptor 1, IFN-␥, and tumor necrosis factor (TNF) receptor 1 (35).…”
Section: Discussionmentioning
confidence: 99%
“…It was reported previously that a lower level of IFNAR1 is associated with a higher risk of liver diseases (54), and polymorphisms of the IFNAR1 promoter are associated with CHB and HCC susceptibility (55,56). IFNAR1 is downregulated by HBx in hepatocytes and in woodchucks infected with WHV (57, 58), indicating that HBV/WHV may establish chronic infection by repressing IFNAR1.…”
Section: Discussionmentioning
confidence: 94%
“…In addition to the identification of SNPs, IFN-γ and IFN-α cytokine expression patterns and genetic variations in the IFN-α receptor subunit 1 (IFN-α r1) might affect clearance rates or contribute to the development of chronicity of early-stage HBV. It may also persistently influence HBV pathogenesis during the chronic long-term infectious process [13]. …”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, several studies found that IFNAR1 gene polymorphisms in promoter, intron and exon regions were associated with HBV infection [13,17,18]. However, data on genes polymorphisms in IFNG (-5A→G), IFNA1 (-2C→T) and IFNAR1 (-97T→C) regions are lacking.…”
Section: Introductionmentioning
confidence: 99%